2016
DOI: 10.30972/vet.262213
|View full text |Cite
|
Sign up to set email alerts
|

<p style="text-align: justify;">A metaphylactic treatment with double dose oxytetracycline reduces the risk of bovine respiratory disease in feedlot calves</p>

Abstract: El objetivo del presente estudio fue evaluar el efecto del tratamiento metafiláctico con oxitetraciclina (OTC), a simple y doble dosis, en bovinos con alto riesgo de padecer enfermedad respiratoria bovina (ERB). El estudio se realizó en un establecimiento de engorde a corral donde se utilizaron 2.754 terneros que fueron considerados de alto riesgo de padecer ERB. Se utilizó un diseño en bloque completamente al azar donde se consideró al animal como la unidad experimental y el corral (n=10) como bloque. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Eighty-five trials from a total of 73 citations reported at least one BRD morbidity outcome. Study selection: excluded because of data extraction issues Seventeen citations had at least one trial in which an arm was excluded from our meta-analysis because of one of the following data issues: multiple arms represented the same treatment, there were zero events in one arm, no extractable data were presented, there was no P-value or baseline risk available for data conversion, the treatment regimen was inadequately described, or the treatment was entirely disconnected from the network (Schipper and Kelling, 1974;Janzen and McManus, 1980;Brown et al, 1989;van Koevering et al, 1992;Guichon et al, 1993;Galyean et al, 1995;Montague et al, 1996;Reece and Smith, 1996;Brazle, 1997;Hibbard et al, 2002;Booker et al, 2006;Booker et al, 2007;Fazzio et al, 2015;Crepieux et al, 2016;Miller et al, 2016;Timsit et al, 2017aTimsit et al, , 2017bFood and Drug Administration, 2018f).…”
Section: Study Selectionmentioning
confidence: 99%
“…Eighty-five trials from a total of 73 citations reported at least one BRD morbidity outcome. Study selection: excluded because of data extraction issues Seventeen citations had at least one trial in which an arm was excluded from our meta-analysis because of one of the following data issues: multiple arms represented the same treatment, there were zero events in one arm, no extractable data were presented, there was no P-value or baseline risk available for data conversion, the treatment regimen was inadequately described, or the treatment was entirely disconnected from the network (Schipper and Kelling, 1974;Janzen and McManus, 1980;Brown et al, 1989;van Koevering et al, 1992;Guichon et al, 1993;Galyean et al, 1995;Montague et al, 1996;Reece and Smith, 1996;Brazle, 1997;Hibbard et al, 2002;Booker et al, 2006;Booker et al, 2007;Fazzio et al, 2015;Crepieux et al, 2016;Miller et al, 2016;Timsit et al, 2017aTimsit et al, , 2017bFood and Drug Administration, 2018f).…”
Section: Study Selectionmentioning
confidence: 99%
“…According to our results metaphylactic treatment with tildipirosin reduced the hazard ratio for BRD (HR=0.26), which means that calves in the TRT group at any individual time along here are 74% less likely to experience an event than the calves in the CTR group. A similar study evaluating the metaphylactic effect of oxytetracycline found a reduced hazard ratio (HR=0.39) and extended 7 days the interval of time from arrival to the diagnosis of BRD in all the calves becoming sick (Fazzio et al, 2015). Tildipirosin in pre-weaned dairy calves has been observed to lower the hazard of being affected with BRD and/or otitis (Teixeira et al, 2017).…”
Section: Discussionmentioning
confidence: 86%